Activators and Effectors of the Small G Protein Arf1 in Regulation of Golgi Dynamics During the Cell Division Cycle - Jackson, Catherine L. (Frontiers in Cell and Developmental Biology, 2018)
When eukaryotic cells divide, they must faithfully segregate not only the genetic material but also their membrane-bound organelles into each daughter cell. To assure correct partitioning of cellular contents, cells use regulatory mechanisms to verify that each stage of cell division has been correctly accomplished before proceeding to the next step. A great deal is known about mechanisms that regulate chromosome segregation during cell division, but we know much less about the mechanisms by which cellular organelles are partitioned, and how these processes are coordinated. The Golgi apparatus, the central sorting and modification station of the secretory pathway, disassembles during mitosis, a process that depends on Arf1 and its regulators and effectors. Prior to total disassembly, the Golgi ribbon in mammalian cells, composed of alternating cisternal stacks and tubular networks, undergoes fission of the tubular networks to produce individual stacks. Failure to carry out this unlinking leads to cell division arrest at late G2 prior to entering mitosis, an arrest that can be relieved by inhibition of Arf1 activation. The level of active Arf1-GTP drops during mitosis, due to inactivation of the major Arf1 guanine nucleotide exchange factor at the Golgi, GBF1. Expression of constitutively active Arf1 prevents Golgi disassembly, and leads to defects in chromosome segregation and cytokinesis. In this mini review, we describe recent advances in understanding the functions of Arf1 regulators and effectors in the crosstalk between Golgi structure and cell cycle regulation.